2018
DOI: 10.1016/j.jds.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Acemannan increased bone surface, bone volume, and bone density in a calvarial defect model in skeletally-mature rats

Abstract: Background/purpose Acemannan, a β-(1–4)-acetylated polymannose extracted from Aloe vera gel, has been proposed as biomaterial for bone regeneration. The aim of this study was to investigate the effect of acemannan in calvarial defect healing. Materials and methods Acemannan was processed to freeze-dried sponge form and disinfected by UV irradiation. Thirty-five female Sprague–Dawley rats were used in the in vivo stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…Godoy et al., revealed that radiation-sterilized acemannan sponges retain their characteristics and bioactivity. 22 …”
Section: Methodsmentioning
confidence: 99%
“…Godoy et al., revealed that radiation-sterilized acemannan sponges retain their characteristics and bioactivity. 22 …”
Section: Methodsmentioning
confidence: 99%
“…Histological observation showed that the bone matrix density of the rats in the polysaccharide treatment group was significantly higher than that of the control group. The results demonstrated that acemannan was an effective natural bioactive substance that promotes bone growth, increases bone surface, bone volume and bone density [88].…”
Section: Acemannan In Wound Healingmentioning
confidence: 99%
“…No fibrous capsule or chronic inflammatory cells were detected in the tooth sockets, furcation defects, or calvarial defects that received acemannan sponges. 18 , 20 , 23 In addition, these other studies showed that acemannan sponges were no longer present in rodent tooth sockets or calvarial defects 1-month post-surgery, and canine furcation defects 2-month post-surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Acemannan was extracted from A. vera gel as previously described. 18 , 20 Briefly, A. vera pulp gel underwent homogenization, centrifugation, precipitation with alcohol, and lyophilization. The white precipitate was characterized by 13 C NMR, 1 H NMR, and FT-IR, which confirmed that the precipitate was acemannan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation